1999
DOI: 10.1083/jcb.144.4.745
|View full text |Cite
|
Sign up to set email alerts
|

Activation of G12/G13 Results in Shape Change and Rho/Rho-Kinase–mediated Myosin Light Chain Phosphorylation in Mouse Platelets

Abstract: Platelets respond to various stimuli with rapid changes in shape followed by aggregation and secretion of their granule contents. Platelets lacking the α-subunit of the heterotrimeric G protein Gq do not aggregate and degranulate but still undergo shape change after activation through thromboxane-A2 (TXA2) or thrombin receptors. In contrast to thrombin, the TXA2 mimetic U46619 led to the selective activation of G12 and G13 in Gαq-deficient platelets indicating that these G proteins mediate TXA2 receptor-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
307
1
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(328 citation statements)
references
References 72 publications
13
307
1
5
Order By: Relevance
“…Interaction of SW480 and CT26 with ADAM10 stimulates RhoA activity As the interaction of Ga13 with RhoA leads to an increase in cell cortical tension as well as in disruption of plasma membrane-cortical actin, 22,23 we investigated whether the interaction of SW480 and CT26 cells with ADAM10Cys-EGFP or ADAM10-EGFP activates Rho small GTPase. To this end, we performed a GTP-RhoA pull-down assay.…”
Section: Adam10 and Cd81 Regulate Localization Of Gtp-binding A13mentioning
confidence: 99%
“…Interaction of SW480 and CT26 with ADAM10 stimulates RhoA activity As the interaction of Ga13 with RhoA leads to an increase in cell cortical tension as well as in disruption of plasma membrane-cortical actin, 22,23 we investigated whether the interaction of SW480 and CT26 cells with ADAM10Cys-EGFP or ADAM10-EGFP activates Rho small GTPase. To this end, we performed a GTP-RhoA pull-down assay.…”
Section: Adam10 and Cd81 Regulate Localization Of Gtp-binding A13mentioning
confidence: 99%
“…The suppressive effect of CT04 on actin aggregation indicates at least partial involvement of Rho activation. Since some Gq coupled receptors have been reported to also interact with G 12/13 signaling [38][39][40][41], it is conceivable that G 12/13 signaling is activated following P2Y 6 receptor stimulation. It was also shown that Rho signaling activated PKCs [18,42,43].…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Rhmentioning
confidence: 99%
“…Both PARs belong to the seven transmembrane family of G-protein linked receptors and have been cloned and sequenced. Both are coupled to Gαq and Gα 12/13 [1]. Thrombin cleaves the receptors within the large N-terminal extracellular domain, creating new amino terminals, SFLLRN and GYPGQV respectively [2,3].…”
Section: Introductionmentioning
confidence: 99%